A phenomenographic approach to research in medical education. Issue 3 (8th February 2013) - Stenfors‐Hayes, Terese; Hult, Hakan; Dahlgren, Madeleine A
<x xml:space="preserve">Abstract</x> Context Phenomenography is a qualitative approach to research which has revolutionised the way that researchers and teachers think about the processes and outcomes of learning in higher education. Phenomenography has also been used successfully in medical and health care research for the last 20 years. Phenomenography provides a lens through which to view certain types of research question. It also provides direction for how to empirically carry out the research. Methods This paper introduces phenomenography as a viable qualitative approach for use in medical education research. Results A phenomenographic study maps the qualitatively different ways in which people experience a phenomenon. This type of study can have an important impact on, for example, patient communication, clinical practice and health care education. Conclusion We suggest that a phenomenographic approach can be used to explore many medical education research issues, and can facilitate more solid links between research and educational development and change.